Analisis Kebijakan Pemerintah Pada Assesmen Kompetensi Minimum (AKM) Sebagai Bentuk Perubahan Ujian Nasional (UN) - Mizanul Hasanah; Tri Fahad Lukman Hakim (LP3M STIT Al Urwatul Wutsqo Jombang, 2021)
The curriculum in Indonesia is a form of equal distribution of education in a country. So, the success of a country in the realm of education depends on the curriculum in that country. In Indonesia, the curriculum has been changing for a long time. The purpose of these changes in the evaluation of the previous curriculum. Since the inauguration of the material for education and culture, many curriculum changes have occurred at all levels, one of which is the National Assessment, namely AKM. Minimum ability assessment (AKM) is a policy of the Ministry of Education and Culture as a substitute for the National Examination (UN). Is this activity successful on target and able to boost the quality of education in Indonesia? It all depends on the implementation of the objectives of AKM activities. The author's purpose is to analyze the AKM activities which this year have been implemented at all levels of education in Indonesia with the theory of policy implementation. Researchers used a literature study approach. The results of the analysis show that the AKM government's policy as a substitute for the National Examination can be accepted by all parties, principals, students, and teachers. Implementation of the Minimum Competency Assessment (AKM) is not based on the ability to master the material according to the curriculum as in the national exam but is designed to map and improve the quality of education as a whole. Minimum Competency Assessment (AKM) focuses on mastering the literacy and numeracy competencies that will be measured.